Pengaruh Pengukusan Terhadap Kualitas Protein Limbah Udang Yang Telah Direndam Dengan Filtrat Abu Sekam - Mirzah Mirzah (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2006)
The use of shrimp head wastes, the by product of shrimp processing, for feedstuff was limited by their protein quality and the present of chitin. The experiment was conducted to examine the effect of steam heat treatments of soaked shrimp head wastes on their protein quality and chitin content. Shrimp heads wastes were first soaked with 10 % of dusk rice husk solution for 48 hours to produce soaked shrimp heads wastes (SHW) product. The SHW product was then treated with steam heat for different periods of 15, 30, 45 and 60 minutes. Parameters measured included crude protein, amino acid, chitin content and protein digestibility. The data were statistically analysis in Completely Randomized Design of 6 x 3. The results showed that steam heat treatment reduced significantly (P<0.01) crude protein and chitin contents of SHW, but digestibility of crude protein (in-vitro) were increased (P<0.01) with increasing length of steam heat.  Concentration of amino acid of SHW was decreased with increasing length of steam heat. Based on comparative cost analysis and their nutritive values the best product was found by SHW treated for 45 min with steam heat.The use of shrimp head wastes, the by product of shrimp processing, for feedstuff waslimited by their protein quality and the present of chitin. The experiment was conductedto examine the effect of steam heat treatments of soaked shrimp head wastes on theirprotein quality and chitin content. Shrimp heads wastes were first soaked with 10 % ofdusk rice husk solution for 48 hours to produce soaked shrimp heads wastes (SHW)product. The SHW product was then treated with steam heat for different periods of 15,30, 45 and 60 minutes. Parameters measured included crude protein, amino acid, chitincontent and protein digestibility. The data were statistically analysis in CompletelyRandomized Design of 6 x 3. The results showed that steam heat treatment reducedsignificantly (P<0.01) crude protein and chitin contents of SHW, but digestibility of crudeprotein (in-vitro) were increased (P<0.01) with increasing length of steam heat.Concentration of amino acid of SHW was decreased with increasing length of steam heat.Based on comparative cost analysis and their nutritive values the best product was foundby SHW treated for 45 min with steam heat.